Perception of health, loneliness, happiness and body image according to type of breakfast during confinement due to Covid-19 - Pedro José Carrillo López (Federación Extremeña de Balonmano; University of Extremadura, 2022)
The aim was to determine the relationship between the perception of health, loneliness, happiness and body image according to the type of breakfast during the state of alarm decreed by the COVID-19 in primary schoolchildren. For this purpose, a descriptive cross-sectional study was designed with a sample of 116 Spanish schoolchildren. Perceptions of health, loneliness, happiness and body image were assessed using four items from the Health Behavior in School-aged Children questionnaire. The items referring to breakfast were extracted from the Mediterranean Diet Quality Index in children and adolescents questionnaire. After inferential analysis, it was observed that eating a cereal or derivative for breakfast was associated with a higher perception of health (OR = 1.45; p = 0.021), happiness (OR = 1.57; p = 0.002), body image (OR = 1.70; p = 0.006), and lower perception of loneliness (OR = 1.74; p = 0.002). This association was maintained after adjustment for body image with the exception of health perception (OR = 1.53, p = 0.156). In conclusion, eating a cereal or derivative for breakfast may be related to a higher perception of health, happiness, body image, and lower perception of loneliness in primary school children.